(untitled) (Bulletin KNOB, 2014)
This article discusses the architecture of Dutch holiday homes built between 1918 and 1940. It analyses how these houses relate to their natural surroundings and to idealized conceptions of holiday life. The study is based on contemporary literature on the design of holiday homes and on a close reading of several architectural examples. In the Netherlands the economic growth of the 1920s, the introduction of summer holidays and the increasing popularity of spending leisure time outdoors contributed to the growing demand for holiday retreats in the woods or moorlands, near the sea, rivers or lakes. Many architects responded to this phenomenon. They designed holiday houses and published books or attractive portfolios on the subject. Local authorities also addressed the new development by establishing regulations for the construction of holiday houses in delicate, natural surroundings. In a densely populated country such as the Netherlands, building in a natural environment often led to a conflict of interests. Stimulating the population to seek outdoor leisure tended to spoil the natural surroundings. By granting temporary building permissions, authorities hoped to keep things under control and be able to reverse unwelcome developments in the future. Several well-known senior publicists on the subject of holiday homes, such as Van der Kloot Meijburg, Leliman and Sluyterman, inspired Dutch architects to design holiday houses that responded to their natural surroundings. Especially Van der Kloot Meijburg had a considerable impact on younger generations of architects, as well as on contemporary construction firms. His urge was to build in a contemporary but rurally inspired idiom, in which ‘honesty’ and ‘modesty’ were considered important values. Van der Kloot Meijburg’s ideas seem to have inspired numerous examples of holiday homes of the period. These houses often resembled small farms, stables or cottages. They were made of wood and had a thatched roof and sparse, small windows. These small houses merged nicely with the natural surroundings, but at the same time they had an introvert character. Experiencing the outside environment from within was often difficult. Some modernist architects criticized this kind of holiday houses. They noted that, instead of adopting rural architectural types for a new type of building, a different architectural language needed to be developed, in particular for clients with an intellectual or artistic, urban background. This belief inspired some of the most famous Dutch holiday homes, such as the summerhouse in Schoorl by B. Merkelbach and Ch. Karsten. This house inverted the traditional concept of the holiday home. The white, cubic volume is a firm statement. It does not seem as if the architects were looking for a refined integration in the natural environment. On the contrary: from the interior, nature can be experienced to the full. Enormous sliding glass walls open to all sides and enable air and light to flow in. Here, experiencing nature is interpreted as a sportive, hygienic activity, as opposed to the romantic interpretation that inspired many dwellings of a more traditional design. Concerning the furnishings of the holiday home, architects – traditionalists as well as modernists – promoted an uncluttered, practical interior with daybeds, movable furniture and combined living-dining-cooking spaces where the inhabitants would be able to free themselves from the distressing, restricted, conventional life in the city.